Pengaruh Analisis Fundamental Terhadap Risiko Sistematis Saham - Denovis, Fanny Oktivia; Arsita, Sari (Program Studi Aktuaria, Fakultas Sains Teknologi dan Pendidikan, Universitas Tamansiswa Padang, 2023)
The purpose of this study was to determine the effect of fundamental analysis, namely Return On Assets (ROA), Return On Equity (ROE), Asset Growth and Earning Per Share (EPS) on the systematic risk of shares proxied by Stock Beta. By using the single-index model in measuring stock beta. The research population is property, real estate, and building construction companies listed on the Indonesia Stock Exchange during the 2016-2018 period. Samples were taken based on a purposive sampling technique with several research samples of 10 companies. The results showed that both partially and simultaneously ROA, ROE, Asset Growth and EPS did not affect the systematic risk of stocks. Determination test results indicate that systematic risk is influenced by ROA, ROE, Asset Grow and EPS of 5.7% and the remaining 94.3% is influenced by other variables outside the research variable.